Values as Motivation Factors of Economic Behaviour - Lačný, Martin (Journal of Economic Development, Environment and People, 2013)
The article presents a reflection on the structure of values functioning as motivators of economic behaviour. Considering the principle of rational egoism the author describes three segments of crucial values, which seem to be fundamental, as a matter of the contemporary Euro-American economic value system – freedom and justice; responsibility and confidence; progress, prosperity and rationality. An important methodological basis of presented reflection is the Ethics of social consequences – dynamically developing consequentialist ethical theory, responding to the challenges arising in the field of applied ethics in the framework of efforts to solve practical problems of today’s world.